Analysis of rainfall of the high rainfall tract of northern agro-climatic zone of Kerala - P A Mathew, K Kandiannan, C K Thankamani, (Journal of Spices and Aromatic Crops, 2008)
Analysis of rainfall of the high rainfall tract of northern agroclimatic zone of Kerala wascarried out for 26 years (1980–2005) to schedule spice crop management practices precisely.The analysis indicated that the tract received 4461 mm of annual rainfall in 145 rainy days.South west monsoon (June to September) alone contributed 75% of annual rainfall and Julywas the rainiest month (1117 mm) with 27 rainy days. The length of growing period wasidentified between 18th standard week to 47th standard week (from 30th April to 25th November)with a mean rainfall of 4284.1 mm. The pre-monsoon period from 2nd April to 6th May (between14th week to 18th week) with a mean rainfall of 180.6 mm was the right time for land preparationfor annual crops like ginger (Zingiber officinale) and turmeric (Curcuma longa) and the periodbetween 30th April to 27th May (18th week to 21st week) with a mean rainfall of 244.4 mm wasideal for planting including first mulching and first schedule of fertilizer application forthese crops. The probability of getting 50 mm rainfall per week was more than 60% duringthe 19th week (7th to 13th May). This is the time for prophylactic plant protection, applicationof first schedule of fertilizer application and shade regulation for black pepper (Piper nigrum)and tree spices. The second schedule of these operations has to be done during the 36th to 39thweek (3rd to 30th September) as this period is relatively rainless (September rainfall was 349.6mm). Though the tract receives high rainfall, there is moisture stress between December andMarch and adequate moisture conservation (or irrigation wherever possible) is essentialparticularly for perennial crops in juvenile stage.